2004
DOI: 10.1002/j.2161-1912.2004.tb00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Acculturation for Chinese Adolescents in Canada: Age of Arrival, Length of Stay, Social Class, and English Reading Ability

Abstract: In a sample of 506 Chinese adolescents living in Canada from 3 cohort groups, age at the time of arrival in Canada, length of stay in Canada, socioeconomic status, and English reading ability predicted acculturation. English reading ability and socioeconomic status predicted acculturative stress. There were within‐group cohort differences in acculturation characteristics. Implications for counseling are addressed. En una muestra de 506 adolescentes Chinos que viven en el Canadá de 3 cohortes, la edad de llegad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
107
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 152 publications
(121 citation statements)
references
References 22 publications
7
107
3
Order By: Relevance
“…Marginalization is the least favorable strategy and can lead to serious mental health problems for individuals. (Constantine et al, 2004;Kuo & Roysircar, 2004;Wei et al, 2007). Coping strategy is another important moderating factor.…”
Section: Berry's Model For Acculturative Stressmentioning
confidence: 99%
See 4 more Smart Citations
“…Marginalization is the least favorable strategy and can lead to serious mental health problems for individuals. (Constantine et al, 2004;Kuo & Roysircar, 2004;Wei et al, 2007). Coping strategy is another important moderating factor.…”
Section: Berry's Model For Acculturative Stressmentioning
confidence: 99%
“…Many studies have reported that Asian students have insufficient English proficiency (e.g., Constantine et al, 2004;Kuo & Roysircar, 2004;Mori, 2000;Yeh & Inose, 2002). In China, children begin to learn English from primary school or even earlier.…”
Section: Acculturative Stress and Cultural Distancementioning
confidence: 99%
See 3 more Smart Citations